Association between operation volume and postoperative mortality in the elective open repair of infrarenal abdominal aortic aneurysms: systematic review - Ronellenfitsch, Ulrich; Meisenbacher, Katrin; Ante, Marius; Grilli, Maurizio; Böckler, Dittmar (Gefässchirurgie, 2020)
An inverse association between the case volume per hospital and surgeon and perioperative mortality has been shown for many surgical interventions. There are numerous studies on this issue for the open treatment of infrarenal aortic aneurysms.
Gesehen am 18.10.2021